Disney's The Lion king. (London : Ravette Books, 1994)
Colorful illustrations and the simple text tell an abbreviated story of Simba, and adventuresome lion cub who learns to find his own place in the Circle of life.
Keywords: Animals -- Fiction; Lions -- Fiction; Simba (Fictitious character: Disney) -- Fiction; Africa -- Fiction